Reproductive factors and cardiometabolic disease among middle-aged and older women: a nationwide study from CHARLS - Wang, Qiong; Pang, Bo; Wu, Jing; Li, Chunyan; Niu, Wenquan (Frontiers in Cardiovascular Medicine, 2024)
Background: Cardiometabolic disease is skyrocketing to epidemic proportions due to the high prevalence of its components and the aging of worldwide population. More efforts are needed to improve cardiometabolic health. The aim of this nationally representative study based on the China Health and Retirement Longitudinal Study (CHARLS, 2014-2018) was to examine the association between reproductive factors and cardiometabolic disease among Chinese women aged ≥45 years.Methods: CHARLS is an ongoing longitudinal study initiated in 2011, and the latest follow-up was completed in 2018. Total 6407 participants were analyzed. Effect-sizes are expressed as odds ratios (OR) and 95% confidence intervals (CI). Confounding was considered from statistical adjustment, subsidiary exploration and unmeasured confounding assessment aspects.Results: Of 6407 accessible participants, 60.9% were recorded to have one or more of five predefined cardiovascular or metabolic disorders. Relative to those with two children, participants who had 0-1 child were found to have a lower risk of cardiometabolic disease (OR=0.844, 95% CI: 0.714-0.998), and those who had ≥3 children had a greater risk (OR=1.181, 95% CI: 1.027-1.357). The onset age of menarche at 16-18 years was a protective factor compared with 16 years of age or below (OR=0.858, 95% CI: 0.749-0.982). By contrast, participants with a history of abortion were 1.212 times more likely to have cardiometabolic disorders (OR=1.212, 95%CI 1.006-1.465). Likelihood for the presence of unmeasured confounding was low, as reflected by E-values.Our findings demonstrated that number of children, age at menarche and history of abortion were associated with the significant risk of cardiometabolic disease among Chinese women aged ≥45 years.